2014
DOI: 10.1103/physreva.90.053807
|View full text |Cite
|
Sign up to set email alerts
|

Control of single-photon transport in a one-dimensional waveguide by a single photon

Abstract: We study controllable single-photon transport in a one-dimensional waveguide with a nonlinear dispersion relation coupled to a three-level emitter in a cascade configuration. An extra cavity field is introduced to drive one of the level transitions of the emitter. In the resonance case, when the extra cavity does not contain photons, the input single photon will be reflected; when the cavity contains one photon, the full transmission of the input single photon can be obtained. In the off-resonance case, the si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…The transport properties of single photons controlled by interaction with atoms (or artificial atoms) inside a onedimensional waveguide have been a subject of considerable interest in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In waveguide quantum electrodynamics (QED) systems, atoms can strongly interact with a continuum of field modes compared with those in free space, and the propagation directions of photons can be well monitored.…”
Section: Introductionmentioning
confidence: 99%
“…The transport properties of single photons controlled by interaction with atoms (or artificial atoms) inside a onedimensional waveguide have been a subject of considerable interest in recent years [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In waveguide quantum electrodynamics (QED) systems, atoms can strongly interact with a continuum of field modes compared with those in free space, and the propagation directions of photons can be well monitored.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, this kind of manipulation can be achieved by coupling a 1D waveguide with a node where the transmission and reflection of the photons can be potentially controlled [1][2][3][4][5][6][7][8][9]. It had been shown that the two-photon transport is strongly correlated in 1D waveguide coupled to a two-level system [1,2] where the strong correlation arises from the interference between the reemitted and scattered waves in the 1D waveguide.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the atom behaves as a quantum switch. Despite having been extensively studied [50][51][52][53][54][55][56], prior work on the coherent transport of photons has typically focused on the nearby CCAs via the photon-atom scattering. However, in order to carry out quantum network operations, information needs to be controllably transported between distant quantum registers.…”
Section: Introductionmentioning
confidence: 99%